The School of Pharmacy, University of London : medicines, science and society, 1842-2012 - Hudson, Briony; Boylan, Maureen (London : Elsevier, 2013)
The School of Pharmacy, University of London: Medicines, Science and Society, 1842-2012 represents the rich history of the University of London School of Pharmacy through numerous color photographs, important advances in the pharmacy profession, cultural milestones, biographies and more. Written in an engaging and authoritative style, this book depicts the chronological history of the school from its establishment in 1842 to the present day with a nod toward its aspirations for the future. By highlighting key periods in the school's history and showing their connection to the wider world, this book truly commemorates the heritage of the School of Pharmacy and its cutting-edge role in pharmacy innovation, research and education. For our ScienceDirect patrons, Elsevier is pleased to announce that complimentary access to the e-book is available on ScienceDirect and has been made possible by sponsorship through the University of London. Upon publication in August, please visit the book's site on ScienceDirect to access the e-book for free.
The Student PopulationLooking to the Future; Afterword: Education for the Future; Appendix: Pharmacy qualifications and courses at the School; Further Reading; Index.
Print version record.
Elsevier
Keywords: University of London. -- School of Pharmacy; University of London. -- School of Pharmacy; Electronic books